Factors that influence consumer credit / Nor Hidayah Mohd Rosly - Mohd Rosly, Nor Hidayah (2014)
This study is carried out to investigate the determinants of the factors that influences to the consumer credit. This study is to identify and analysis what the factor that influences to the consumer credit to the people or consumer that apply for the consumer credit in their life. This matter is important for the people that have consumer credit especially in their future. It also will give information the relationship consumer credit with personal finance, social lifestyle and the individual lifestyle. General objective of the study is to investigate the factor that influence to the consumer credit. While the specific objectives of the study are to determine the personal finance that give influence to the consumer credit, to examine the personal lifestyle factors that influence to the consumer credit and to identify the individual attitude factor that influence to the consumer credit. On this research, the random person has been chosen as the sample of this research in order to analyze the topics. At the end, the results show that the most factors that influences to the consumer credit is personal finance factor. While the social lifestyle and the individual attitude factors not give influence to the consumer credit.